2010
DOI: 10.1590/s0100-40422010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Retenção de metais pesados em micélio de fungos micorrízicos arbusculares

Abstract: Recebido em 26/8/08; aceito em 7/6/09; publicado na web em 27/11/09 RETENTION OF HEAVY METALS BY ARBUSCULAR MYCORRHIZAL FUNGI MYCELIUM. This work evaluated the kinetics as well as the retention capacity of Cu, Zn, Cd, and Pb by arbuscular mycorrhizal fungi (AMF) mycelium. The metal retention is a fast process with Cu being retained 3, 30, and 60 times faster than Zn, Cd, and Pb, respectively. Metal retention capacity varied amongst the different tested AMF species and decreased in the following order: Cu>Zn>>C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
0
5
0
7
Order By: Relevance
“…This result could be related to a decreased Cu absorption due to the retention and immobilization of the metal in the cellular wall components of the intra and extraradical hyphae or compartmentalization of the metal in the interior of the fungal cells (Khan et al, 2000;Zhu et al, 2001;Aguilera et al, 2011;Meier et al, 2011Meier et al, , 2012aCornejo et al, 2013), reducing Cu transfer to the AM colonized plant. The results obtained by Cabral et al (2010) demonstrated the myceliuns of R. clarus has the capacity to retain higher quantities of Cu compared to Zn, Cd or Pb, corroborating that this AMF can excludes this element outside the root cell and limits plant exposure to it. Additionally, glycoproteins produced by AMF can effectively retain heavy metal in high amounts in the soil, therefore reducing the availability of the contaminants to the plants, with a subsequent plant protective effect.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This result could be related to a decreased Cu absorption due to the retention and immobilization of the metal in the cellular wall components of the intra and extraradical hyphae or compartmentalization of the metal in the interior of the fungal cells (Khan et al, 2000;Zhu et al, 2001;Aguilera et al, 2011;Meier et al, 2011Meier et al, , 2012aCornejo et al, 2013), reducing Cu transfer to the AM colonized plant. The results obtained by Cabral et al (2010) demonstrated the myceliuns of R. clarus has the capacity to retain higher quantities of Cu compared to Zn, Cd or Pb, corroborating that this AMF can excludes this element outside the root cell and limits plant exposure to it. Additionally, glycoproteins produced by AMF can effectively retain heavy metal in high amounts in the soil, therefore reducing the availability of the contaminants to the plants, with a subsequent plant protective effect.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies done in vitro with the AMF Rhizophagus clarus (T.H. Nicolson & N.C. Schenck) C. Walker & A. Schüßler have demonstrated a differentiated capacity of the fungus to retain Cu, Zn, Cd, and Pb in the mycelium (Cabral et al, 2010). This behavior was attributed to the differential production of glomalin, however the role of this protein has not been experimentally evaluated in tropical soils containing excessive levels of PTE.…”
Section: Introductionmentioning
confidence: 99%
“…Como os efeitos das micorrizas no crescimento de plantas são dependentes das espécies e dos isolados fúngicos (CABRAL et al, 2010), é importante selecionar isolados de fungos ectomicorrízicos que possibilitem aumento significativo de produtividade (ALVES et al, 2001). Nesse sentido, o objetivo deste trabalho foi avaliar o efeito dos isolados ectomicorrízicos UFSC-Pt116, UFSC-121, UFSC-132 no crescimento de mudas de Eucalyptus grandis, Corymbia citriodora, Eucalyptus saligna e Eucalyptus dunnii em condições de viveiro.…”
Section: Introductionunclassified
“…Atualmente, o mecanismo que envolve a ação de FMAs na proteção das plantas em solos contaminados é conhecido como micorremediação, e tem sido objeto de estudo visando a sua utilização em programas de revegetação de áreas contaminadas por metais (NOGUEIRA, 2007;SOARES, 2010). Apesar dos mecanismos do FMAs na estabilização dos metais pesados, ainda não estarem elucidados, pesquisas sugerem que existe maior retenção dessas substâncias no micélio fúngico, por adsorção e fixação em grânulos de polifosfato, protegendo a planta contra o excesso de metais e aumentando a estabilidade dos agregados no solo (HALL, 2002;OLGUÍN et al, 2007;KERBAUY, 2012).…”
Section: Introductionunclassified